The Relationship between School Moral Atmosphere and Student Engagement in Secondary Schools - Akarsu, Nesli; Turhan, Muhammed (Asya Publishing and Consultancy, 2022)
The main aim of the study is to examine the relationship between the secondary school students’ perceptions of the school’s moral atmosphere and their engagement with school. The School Engagement Scale and School Moral Atmosphere Scale were applied to 872 students attending the secondary schools in the 2016-2017 academic year. The study revealed that the school engagement levels showed a significant difference in favor of female students in terms of gender. Based on the multiple regression analysis, it was determined that school moral atmosphere is a significant predictor of school engagement. The results of this study suggest that school moral atmosphere is one of the key determinants of students’ engagement with school, and hence it can be useful to improve school moral atmosphere to increase students’ affective, cognitive, and behavioral engagement. © 2022, Asya Publishing and Consultancy. All rights reserved.
Keywords: School moral atmosphere; Secondary school; Student engagement with school